2017
DOI: 10.3390/jof3020024
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Species Distribution and Antifungal Susceptibility of Candida Bloodstream Isolates from Latin American Medical Centers

Abstract: The epidemiology of candidemia varies geographically, and there is still scarce data on the epidemiology of candidemia in Latin America (LA). After extensive revision of medical literature, we found reliable and robust information on the microbiological aspects of candidemia in patients from 11 out of 21 medical centers from LA countries and 1 out of 20 from Caribbean countries/territories. Based on 40 papers attending our search strategy, we noted that C. albicans remains the most common species causing candi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
49
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(64 citation statements)
references
References 82 publications
6
49
0
9
Order By: Relevance
“…The global impact of Candida infections is enormous ( Quindós, 2014 ; Enoch et al, 2017 ) although the epidemiology of the species involved in the invasive diseases is constantly changing as it depends on many factors including the geographical region considered, patient population, antifungal prophylaxis, diagnostic tests, and local hospital-related characteristics ( Guinea, 2014 ; Quindós, 2014 ; Caggiano et al, 2015 ; Prigitano et al, 2016 ; Enoch et al, 2017 ; Epelbaum and Chasan, 2017 ). In this context, C. tropicalis has emerged as the predominant NAC species causing candidemia, especially in East Asian and Latin American countries ( Yesudhason and Mohanram, 2015 ; Wang et al, 2016 ; da Matta et al, 2017 ; Motoa et al, 2017 ; Wu et al, 2017 ). In these countries, an extraordinary high incidence of C. tropicalis has also been recently reported from natural environments and animals ( Chi et al, 2012 ; Brilhante et al, 2015 ; Cordeiro Rde et al, 2015 ; Zuza-Alves et al, 2016 ) by representing a potential threat to humans living in these geographical areas.…”
Section: Discussionmentioning
confidence: 99%
“…The global impact of Candida infections is enormous ( Quindós, 2014 ; Enoch et al, 2017 ) although the epidemiology of the species involved in the invasive diseases is constantly changing as it depends on many factors including the geographical region considered, patient population, antifungal prophylaxis, diagnostic tests, and local hospital-related characteristics ( Guinea, 2014 ; Quindós, 2014 ; Caggiano et al, 2015 ; Prigitano et al, 2016 ; Enoch et al, 2017 ; Epelbaum and Chasan, 2017 ). In this context, C. tropicalis has emerged as the predominant NAC species causing candidemia, especially in East Asian and Latin American countries ( Yesudhason and Mohanram, 2015 ; Wang et al, 2016 ; da Matta et al, 2017 ; Motoa et al, 2017 ; Wu et al, 2017 ). In these countries, an extraordinary high incidence of C. tropicalis has also been recently reported from natural environments and animals ( Chi et al, 2012 ; Brilhante et al, 2015 ; Cordeiro Rde et al, 2015 ; Zuza-Alves et al, 2016 ) by representing a potential threat to humans living in these geographical areas.…”
Section: Discussionmentioning
confidence: 99%
“…The attributable mortality rate (25–60%) of patients with candidemia varies from 25 to 60%, with significant higher rates among developing countries ( Kaur and Chakrabarti, 2017 ). Candida albicans is usually the most frequently involved species in cases of candidemia ( Arendrup, 2013 ; da Matta et al, 2017 ; Fu et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, recent studies have reported that the abdominal cavity and mucosal surfaces may serve as reservoirs for resistant isolates (8,9). Echinocandins are indicated to be the first line of treatment in cases of invasive candidiasis (10), a recommendation supported by the low rate of echinocandin resistance (1,11,12). However, some studies have provided alerts on the increased rates of echinocandin resistance in C. glabrata strains causing infection in some geographic areas (4,5).…”
mentioning
confidence: 99%